Phytoremediation of Nitrogen as Green Chemistry for Wastewater Treatment System - Lennevey, Kinidi; Shanti Faridah, Salleh (Hindawi Publishing Corporation, 2017)
It is noteworthy that ammoniacal nitrogen contamination in wastewater has reportedly posed a great threat to the environment. Although there are several conventional technologies being employed to remediate ammoniacal nitrogen contamination in wastewater, they are not sustainable and cost-effective. Along this line, the present study aims to highlight the significance of green chemistry characteristics of phytoremediation in nitrogen for wastewater treatment.Notably, ammoniacal nitrogen can be found in many types of sources and it brings harmful effects to the environment.Hence, the present study also reviews the phytoremediation of nitrogen and describes its green chemistry characteristics. Additionally, the different types of wastewater contaminants and their effects on phytoremediation and the phytoremediation consideration in wastewater treatment application and sustainable waste management of harvested aquatic macrophytes were reviewed. Finally, the present study explicates the future perspectives of phytoremediation. Based on the reviews, it can be concluded that green chemistry characteristics of phytoremediation in nitrogen have proved that it is sustainable and cost-effective in relation to other existing ammoniacal nitrogen remediation technologies. Therefore, it can be deduced that a cheaper and more environmental friendly ammoniacal nitrogen technology can be achieved with the utilization of phytoremediation in wastewater treatment.